ANALISIS FAKTOR RISIKO KELELAHAN KERJA PADA PEKERJA LEPAS PANTAI INDUSTRI MINYAK DAN GAS - Nikita Bella Anastasia; Indri Hapsari Susilowati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
The construction of offshore platforms that aims to support the process of exploration or exploitation of oil and gas has a high risk because workers carry out activities on board for a certain period. Fatigue is a condition where there is a decrease in efficiency and endurance at work. Workload and individual characteristics are one of the factors supporting the occurrence of fatigue so that the workload received must be following the physical and mental abilities of workers which are analyzed based on the individual characteristics of workers. Work-related fatigue significantly affects worker capacity and can impact worker performance. This research method is a literature study based on previous studies by adjusting the criteria to the variables studied. In this study, it was found that workload risk factors and individual characteristics can increase worker fatigue which results in several physical diseases such as asthma, high blood pressure, heart, kidney, and mental disorders such as stress, depression, and anxiety disorders.